(untitled) (diségno, 2018)
Since several years, a regular biennial appointment is the International Congress of Expresión Gráfica Arquitectónica (EGA), now in its XVII edition, and held at the Universidad Politécnica of Alicante, organized by the Spanish teachers of the drawing area, in this case belonging to the Departamento de Expresión Gráfica, Composición y Proyectos of the same university. The study days took place on 30th and 31st May and 1st June within the San Vicente del Raspeig campus, a university complex that, built in the area of the dismissed military airport, hosts several pavilions, the result of design competition which was attended by architects as Álvaro Siza Vieira, who designed the rectorate, and Alberto Campo Baeza, author of the library building (read more).